TEACHING PHILOSOPHY, GROWING CHILD’S EMPATHY : DERRIDA’S TRACE THEORY FOR CRITICAL THINKING AND CHARACTER EDUCATION - Fraya, Fatimah; Hadinata, Fristian (International Review of Humanities Studies, 2025)
Child bullying cases increased significantly following the pandemic and took its toll on the need for emergency tackling and preventive action. This research focused on philosophy as a an approach to character building, using the synthesis method of literature views which also inspired from previous teachings known as Philosophy for Children (P4C), combined with hands-on experiment simulation. The aim is to discover a practical learning concept to enable philosophy to be introduced in children's classrooms at a certain age. Researchers found the intersection between philosophy and child character building beneficial in refining their empathy cognitively and creating better generations in avoidance of abusive behavior as part of their day-to-day education. In the discussion, philosophy was introduced choosing the ideas of Jacques Derrida which are considered relevant. Reflective to his childhood, in which Derrida had experienced discrimination, the experience evolved in his breakthrough ideas of hermeneutics, using the deconstruction technique. The simulation experiment study shall revolve around Derrida’s Trace Theory and Différance, both a refreshing concept as learning materials. The result is a recommendation that philosophy worth being considered as an instrument of learning activity in Indonesia’s classroom, using simulation method that can invoke further curiosity in children’s critical thinking and character education.